ANALISIS SELF EFFICACY PESERTA DIDIK DALAM PEMBELAJARAN MATEMATIKA DENGAN MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE, SHARE - Azzahra, Bilqis Aulia; Fitriza, Rozi; Mardika, Fitria (Math Educa Journal, 2023)
Self efficacy is a basic belief in learning, especially learning mathematics, because self efficacy can have a strong effect that can show students' self-confidence, when students have a high self-efficacy category, students can solve problems in learning mathematics well. This study aims to analyze the self efficacy of students in learning mathematics with the Search, Solve, Create, Share (SSCS) learning model. This research is a descriptive quantitative research. The subjects in the study were students of class VIII SMPN 8 Bukittinggi and a sample of 30 people. The instrument used is a self efficacy questionnaire. The data analysis technique uses descriptive statistical analysis using the percentage of degrees of achievement. The results of the study were obtained that the self efficacy of students with the learning model given search, solve, create share there were 8 students in the high category, 21 students in the high enough category, and 1 student in the medium category. While overall the degree of achievement of students' self efficacy is in the high enough category. Where for each dimension of students' self efficacy is also in the high enough category.